2016
DOI: 10.1123/jmld.2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual Coordination Development Is Enhanced in Young Females and Experienced Athletes

Abstract: We characterize bimanual coordination development for the first time in a large sample of children (n = 303) in relation to age, sex, and athletic experience. A further aim is to document the effect of these factors on development to indirectly gain insight into the neural processes that underlie this advanced level of eye–hand coordination. This was a cross-sectional design involving three age groups (range: 9–15 years) that were further separated by sex and level of athletic experience. Participants complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Potential age-related effects may have been washed out because of the large sports-related experience range (1-12 years) in a group with a relatively smaller age range (8-15 years). A few other studies have reported sex-related differences in children and adults for bimanual and complex eye-hand coordination tasks, as well as in concussion rates and symptom-related recovery post-concussion (Albines et al, 2016;Black, Cat, Sergio, & Macpherson, 2016;Gorbet & Sergio, 2007;Karlin, 2011;Lenroot & Giedd, 2010). However, we did not find effects of sex on CMI recovery or performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Potential age-related effects may have been washed out because of the large sports-related experience range (1-12 years) in a group with a relatively smaller age range (8-15 years). A few other studies have reported sex-related differences in children and adults for bimanual and complex eye-hand coordination tasks, as well as in concussion rates and symptom-related recovery post-concussion (Albines et al, 2016;Black, Cat, Sergio, & Macpherson, 2016;Gorbet & Sergio, 2007;Karlin, 2011;Lenroot & Giedd, 2010). However, we did not find effects of sex on CMI recovery or performance.…”
Section: Discussioncontrasting
confidence: 99%
“…Age is another potentially relevant recovery factor since complex cognitive–spatial abilities (which are crucially relevant for cognitive–motor integration) emerge later in development than simple goal‐directed reaching abilities (Lubans, Morgan, Cliff, Barnett, & Okely, 2010; Paus, 2005), possibly leading to faster CMI performance recovery in adolescents than in younger children. There are also sex‐related differences in eye–hand coordination development and performance (Albines, Granek, Gorbet, & Sergio, 2016; Gorbet & Sergio, 2007), which may lead to different CMI recovery times between girls and boys. Therefore, in the present study, we examine factors that may influence the recovery of CMI performance in youth with a history of concussion, such as age, sex, number of concussions, and years of sport experience in eye–limb coordination sports.…”
Section: Introductionmentioning
confidence: 99%
“…(33)(34)(35) Thus, while the current study's effects are subtle, we believe these data indirectly support the idea that this type of activity (controlled visuomotor exercises that integrate explicit an implicit cognitive rules for successful performance) is useful for augmenting functional brain networks shown to be impaired in those at risk for developing dementia. (5,(15)(16)(17)(18) It is important to note that previous work on bimanual coordination has found a large sex-related difference in performance on these types of tasks (30,(36)(37) and differences in visuomotor control more generally. (38)(39)(40) While there was an overall difference in male to female ratio for our participants, we do not believe that the improvements we observed here were driven solely by the "female advantage" for bimanual tasks, since the only group to show improvement was the atrisk training group (1:4 male:female ratio) and not the healthy training group (6:6 male:female ratio) nor the no-training groups.…”
Section: Discussionmentioning
confidence: 97%
“…The Bimanual Coordination Task (30) is a timed task that involves switching between left and right hands to serially pick up a lever and move a washer onto a peg (see Figure 3).…”
Section: Bimanual Coordination Taskmentioning
confidence: 99%
“…In addition, on an explanatory basis and based on the results shown in Figure 2 and existing literature of eye-hand coordination development in youth (e.g. (Albines, Granek, Gorbet, & Sergio, 2016), we examined the time course of Direct interaction and Eye-hand-decoupled development across Young children (8-10 years), Children (11-12 years), and Adolescents (13-15 years). For all dependent measures (cf., above), effects of group (Young children, Children, Adolescents) and condition (Direct, Eye-hand-decoupled) were analyzed using a repeatedmeasures mixed ANOVA, with group (Young children, Children, Adolescents) as a between-subjects factor and condition (Direct, Decoupled) as a within-subjects factor.…”
Section: Discussionmentioning
confidence: 99%